Potable Water Reuse in Small Inland Communities: Oasis or Mirage?. Issue 4 (6th April 2020) - Scruggs, Caroline E.; Lawler, Desmond F.; Tchobanoglous, George; Thomson, Bruce M.; Schwarzman, Megan R.; Howe, Kerry J.; Schuler, Andrew J.
Key Takeaways: Potable reuse can benefit communities with threatened water supplies, but barriers to implementation exist, particularly for smaller communities. Among the challenges associated with potable reuse, the potential health risks of unregulated chemical contaminants found in treated wastewater deserve more attention. Gaps in research and policy regarding contaminants of emerging concern need to be addressed before treated wastewater is used to expand the potable water supplies of smaller communities.